ANALISIS PENERAPAN TARGET COSTING UNTUK PENGENDALIAN BIAYA SERVICE ( Studi Kasus Pada CV. Mahakam Jaya Safety ) - -, Widya Lestari (EKONOMIA, 2017)
Target costing is determining the expected cost of a product based on competitive prices, so that the product will be able to obtain the expected profit. This study aims to find out the process of cost control service using target costing system and its impact on corporate profits. The research was conducted on the CV. Mahakam Jaya Safety which is located in the village of Sungai Pinang in Jl. A proclamation no. 78 Samarinda. CV. Mahakam Jaya Safety is one of the companies engaged in services which service tube fire extinguishers or a fire extinguisher. Pursuant to the results of research conducted, the authors conclude that the presence of target costing, the company can exercise control over the cost better than the method which has been used by the company. Proven by an increase in profits from the company.